2011
DOI: 10.1093/bja/aer295
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of the A.P. Advance, McGrath, and Macintosh laryngoscopes in normal and difficult intubation scenarios: a manikin study

Abstract: Experienced anaesthetists required a longer time for intubation in a standard manikin using a McGrath compared with other laryngoscopes, but a shorter time for intubation in a difficult manikin using an APA with DAB, and with fewer glottic advances, compared with other laryngoscopes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 23 publications
(18 reference statements)
2
25
0
1
Order By: Relevance
“…We thought that difficulties in dealing with the handle of the laryngoscope or the stylet were likely to have increased the intubation time after exposing the glottis. A previous study demonstrated that the time to view the vocal cords with the McGrath is shorter than with the Macintosh and that the time to intubate, except for the time to view the vocal cords, is longer than in the Macintosh [20]. Moreover, we studied novice intubators who were not skilled in eye-hand coordination and had difficulty intubating with the indirect view of the GlideScope [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thought that difficulties in dealing with the handle of the laryngoscope or the stylet were likely to have increased the intubation time after exposing the glottis. A previous study demonstrated that the time to view the vocal cords with the McGrath is shorter than with the Macintosh and that the time to intubate, except for the time to view the vocal cords, is longer than in the Macintosh [20]. Moreover, we studied novice intubators who were not skilled in eye-hand coordination and had difficulty intubating with the indirect view of the GlideScope [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, of the many possible airway situations, we tested only normal simulated airways, including cervical immobilization with a neck collar [20]. Difficult airway situations, such as pharyngeal obstruction and tongue edema, were not investigated [22].…”
Section: Discussionmentioning
confidence: 99%
“…[8] and Burdett et al . [9] found in manikin studies that in difficult airway scenario using cervical spine immobilisation, McGrath video laryngoscope offered better laryngoscopic view using Cormack and Lehane grading as compared with Macintosh laryngoscope. They explained, that with a direct laryngoscope it is necessary to obtain a line of sight from the maxillary teeth to the glottis, which is difficult to obtain using cervical spine immobilisation technique, whereas with the use of McGrath video laryngoscope the image of glottis is captured near the tip of the blade, only a few centimetres of line of sight is required and the need to align the oral, pharyngeal and laryngeal axes is not there.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Burdett et al . [9] found in a manikin study that in difficult airway scenario McGrath video laryngoscope required less time for intubation as compared with Macintosh laryngoscope.…”
Section: Discussionmentioning
confidence: 99%
“…[10] The McGrath videolaryngoscope (Aircraft Medical, Ltd, Edinburgh, UK) has a liquid-crystal display (LCD) screen on the top of its handle and a slim acrylic cover with a 60° angulation which provides an indirect view of the glottis. [11] In this study, we aimed to compare the performances of novices using direct and indirect laryngoscopes.…”
mentioning
confidence: 99%